The acquisition of Chinese firms: from the combination of Institution and OLI perspective - zhang, lili (2017)
This paper aims to investigate the acquisitions of Chinese firms with the rapid foreign investment development of Chinese firms under the home country institutional environment. Institution perspective is mainly divided into three parts normative, regulative and coercive. It should be combined with previous resource and industry view to better explain the FDI of Chinese firms. On the one hand, the institutional environment in China could provide Chinese firms the special advantages even the lack of world-class management and knowledge compared with counterparts from advanced economies. Those advantages include the political and economic support from government and ‘spillover” that got through the joint venture with advanced partners in the home country. On the other hand, the institutional constraints such as poor property protection and low-quality brand image in China will also force Chinese firms to invest overseas to pursue sufficient institutional environment. This could combine with OLI model to better explain the internationalization of Chinese firms. In the case studies, the two Chinese firms took acquisition strategies as a shortcut to acquire advanced technology and management. This essay focus on the pull and push force of institution. It plays a more and more important role in the internationalization of firms and should be considered by company managers in the future.